Targeting CSC-immune cell crosstalk to overcome chemoresistance and enhance immunotherapy efficacy - Yu, Guanxiao; Gong, Jianbao (Frontiers in Immunology, 2025)
Cancer stem cells (CSCs) are a subpopulation of tumor cells that play crucial roles in driving tumor recurrence, metastasis, and resistance to therapies, including chemotherapy and immunotherapy. Growing evidence suggests that interactions between CSCs and immune cells, particularly tumor-associated macrophages, myeloid-derived suppressor cells, and regulatory T cells, create a supportive tumor microenvironment conducive to immune evasion and chemoresistance. Understanding these intricate crosstalk mechanisms, mediated via cytokines, exosomes, and metabolic intermediates, is crucial for the development of effective therapeutic strategies. Here, we comprehensively review recent progress on CSC-immune cell crosstalk, highlighting key signaling pathways and molecular targets. Furthermore, we discuss promising clinical strategies combining conventional therapies with interventions targeting CSC-immune interactions, aiming to enhance immunotherapy efficacy and overcome therapeutic resistance in cancer patients.